Polycyclic aromatic hydrocarbons and heavy metals in some Nigerian commercial meats: a public health concern? - Eridiong O. Onyenweaku (Ibom Medical Journal, 2025)
Background: Various chemical compounds enter food during meat production, processing, and storage. With increasing urbanization and industrialization, environmental pollution is also rising, posing a public health concern.